2011
DOI: 10.1177/1090820x10391395
|View full text |Cite
|
Sign up to set email alerts
|

The Sentinel Fat Pads: The Relationship of the ROOF and SOOF to the Temporal Nerve in Facial Rejuvenation

Abstract: The ROOF was formerly unrecognized as an important sentinel marker for possible injury to the temporal nerve branch during browlift. However, this cadaver study and its accompanying literature comparisons show that browlift dissection, whether endoscopic or open, should aim to keep the ROOF fat in the superficial plane, ensuring that the nerve branch is safe from iatrogenic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…This is in agreement with several previous anatomic studies that found 1 to 4 branches of the temporal branch of median nerve with a median of 3 branches. 2,9,15,16,12,14,17,18,4,19,20,5,6,21 In the temporal region, the layer of the temporal fascia in which the TBFN lies is another controversial and perplexing topic. We found 21 studies that looked at the course of TBFN in the temporal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with several previous anatomic studies that found 1 to 4 branches of the temporal branch of median nerve with a median of 3 branches. 2,9,15,16,12,14,17,18,4,19,20,5,6,21 In the temporal region, the layer of the temporal fascia in which the TBFN lies is another controversial and perplexing topic. We found 21 studies that looked at the course of TBFN in the temporal region.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve was reported to be either within the deepest part of TPF or deep to the TPF, in all studies. 10,22,11,2,23,14,7 Abul-Hassan et al 10 reported that it was found deep to the TPF in a pocket of fat between superficial and deep layer of deep temporal fascia. Above the zygomatic arch, it was most commonly found deep to the TPF.…”
Section: Discussionmentioning
confidence: 99%
“…However, this description was based on intraoperative findings, and the limited operative field prevented the anatomy of the ROOF from being fully explored (15). The relationships between the ROOF layer and other important structures in the periorbital region, including lateral orbital thickening, deep temporal fascia, and the zygomatio-temporal nerve, have only recently been elucidated (16).…”
Section: Discussionmentioning
confidence: 99%
“…10,11,21 More recent reports, however, have confirmed the frontal branch to have between two and five rami crossing the central third to half of the zygomatic arch. 14,17,21 Moreover, some of these reports have found that there is arborization between the various rami of the frontal nerve but not with other branches of the facial nerve. 14 Nevertheless, the interconnections between the rami can likely explain the return of function by 6 months often seen after inadvertent injury.…”
Section: Frontal Branch Anatomymentioning
confidence: 98%
“…26,27 In a recent article, Singh et al described the depth of the nerve relative to the sub-orbicularis oculi fat pad and retro-orbicularis oculi fat pad. 28 They found that the frontal branch passes lateral to the suborbicularis oculi fat pad and lies just superficial to the retro-orbicularis oculi fat pad and therefore dissection deep to this plane would keep the nerve protected. The retro-orbicularis oculi fat pad is contiguous with the sub-SMAS fat, therefore again confirming the safety of dissection deep to loose areolar tissue just above the deep temporal fascia.…”
Section: Frontal Branch Anatomymentioning
confidence: 99%